The Effect of Elevated CO2 and Increased Temperature on in Vitro Fertilization Success and Initial Embryonic Development of Single Male:Female Crosses of Broad-Cast Spawning Corals at Mid- and High-Latitude Locations - Miriam Schutter; Yoko Nozawa; Haruko Kurihara (Journal of Marine Science and Engineering, 2015)
The impact of global climate change on coral reefs is expected to be most profound at the sea surface, where fertilization and embryonic development of broadcast-spawning corals takes place. We examined the effect of increased temperature and elevated CO2 levels on the in vitro fertilization success and initial embryonic development of broadcast-spawning corals using a single male:female cross of three different species from mid- and high-latitude locations: Lyudao, Taiwan (22° N) and Kochi, Japan (32° N). Eggs were fertilized under ambient conditions (27 °C and 500 μatm CO2) and under conditions predicted for 2100 (IPCC worst case scenario, 31 °C and 1000 μatm CO2). Fertilization success, abnormal development and early developmental success were determined for each sample. Increased temperature had a more profound influence than elevated CO2. In most cases, near-future warming caused a significant drop in early developmental success as a result of decreased fertilization success and/or increased abnormal development. The embryonic development of the male:female cross of A. hyacinthus from the high-latitude location was more sensitive to the increased temperature (+4 °C) than the male:female cross of A. hyacinthus from the mid-latitude location. The response to the elevated CO2 level was small and highly variable, ranging from positive to negative responses. These results suggest that global warming is a more significant and universal stressor than ocean acidification on the early embryonic development of corals from mid- and high-latitude locations.